A systematic review of butterfly pea flower (Clitoria ternatea L.): extraction and application as food freshness pH-indicator for polymer-based intelligent packaging - Hasanah, Nur Nabilah; Mohamad Azman, Ezzat Mohamad; Rozzamri, Ashari; Zainal Abedin, Nur Hanani Zainal; Ismail-Fitry, Mohammad Rashedi (Multidisciplinary Digital Publishing Institute, 2023)
The butterfly pea flower (Clitoria ternatea L.) (BPF) has high anthocyanin content, which can be incorporated into polymer-based films to produce intelligent packaging for real-time food freshness indicators. The objective of this work was to review systematically the polymer characteristics used as the BPF extract carriers and their application on various food products as intelligent packaging systems. This systematic review was developed based on the scientific reports accessible on the databases provided by PSAS, UPM and Google Scholar between 2010 to 2023. It covers the morphology, anthocyanins extraction, and applications of anthocyanins-rich colourants from butterfly pea flower (BPF) and as pH indicators in intelligent packaging systems. Probe ultrasonication ex-traction was successfully employed to extract a higher yield which showed a 246.48 better extraction of anthocyanins from BPF for food applications. In comparison to anthocyanins from other natural sources, BPF has a major benefit in food packaging due to its unique colour spectrum throughout a wide range of pH values. Several studies reported that the immobilisation of BPF in different polymeric film matrixes could affect their physicochemical properties but still effectively able to monitor the quality of perishable food in real-time. In conclusion, the development of intelligent films employing BPF's anthocyanins is a potential strategy for the future of the food packaging system.